Exact and kernelization algorithms for Closet String - Latorre Vilca, Omar (2020)
In this paper we address CLOSEST STRING problem that arises in web searching, coding theory and computational molecular biology. To solve it is to find a string that minimizes the maximum Hamming distance from a given set of strings. CLOSEST STRING is an NP-hard problem. This paper proposes two linear-time algorithms, one for the general case, a kernelization algorithm, and the other for three-strings, a linear-time algorithm called Minimization First Algorithm (MFA). A formal proof of the correctness and the computational complexity of the proposed algorithms are given.